The science of ghosts - Sturges, Lilah (Legendary Comics, 2024)
After her transition, Joy Ravenna has settled into a comfortable life with her girlfriend Cat and works as a forensic parapsychologist. Her goal: make the world believe that ghosts are real and are vital to solving crimes. When the heir to the Haskell Firearms business empire Liz Haskell is mysteriously murdered at her home, Joy is called in to investigate.--